2012
DOI: 10.1108/09684881211240295
|View full text |Cite
|
Sign up to set email alerts
|

Investigating attrition trendsin order to improvestudent retention

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
0
32
0
2
Order By: Relevance
“…Otras causas que destacan los investigadores: problemas tecnológicos (Frankola, 2001;Dupin-Bryant, 2004); las rigideces curriculares, la elección errónea de la carrera o acceder con expectativas equivocadas (Grebennikov y Shah, 2012); motivos económicos y sociales y la dificultad de los estudios (Duque, Duque y Surinach, 2013); la baja autoestima del estudiante (Roso-Bas, Pades y García, 2016); los bajos niveles de supervisión y apoyo docente (Montalvo, 2012); la escasa motivación, inadecuados diseños pedagógicos de las asignaturas y la baja cualificación de los docentes (Frankola, 2001); la escasa calidad de los programas con contenido relevante poco estructurados (Ivankova y Stick, 2007;Perry, Boman, Care, Edwards y Park, 2008); la falta de retroalimentación docente, la gran carga de trabajo y las dificultades para estudiar lejos del campus (Choi, Lee, Jung y Latchem, 2013). Por su parte, Fozdar, Kumar y Kannan (2006) ordenan las causas de abandono de esta manera: lejanía del centro de estudios, insuficiente apoyo académico, problema del tiempo de estudio, dificultad de asistir a los laboratorios, ausencia de interacción entre pares, dificultades para estudiar ciencias a distancia, dificultad del examen presencial, escasa capacidad de respuesta del centro de estudios.…”
Section: Los Resultados Las Causasunclassified
“…Otras causas que destacan los investigadores: problemas tecnológicos (Frankola, 2001;Dupin-Bryant, 2004); las rigideces curriculares, la elección errónea de la carrera o acceder con expectativas equivocadas (Grebennikov y Shah, 2012); motivos económicos y sociales y la dificultad de los estudios (Duque, Duque y Surinach, 2013); la baja autoestima del estudiante (Roso-Bas, Pades y García, 2016); los bajos niveles de supervisión y apoyo docente (Montalvo, 2012); la escasa motivación, inadecuados diseños pedagógicos de las asignaturas y la baja cualificación de los docentes (Frankola, 2001); la escasa calidad de los programas con contenido relevante poco estructurados (Ivankova y Stick, 2007;Perry, Boman, Care, Edwards y Park, 2008); la falta de retroalimentación docente, la gran carga de trabajo y las dificultades para estudiar lejos del campus (Choi, Lee, Jung y Latchem, 2013). Por su parte, Fozdar, Kumar y Kannan (2006) ordenan las causas de abandono de esta manera: lejanía del centro de estudios, insuficiente apoyo académico, problema del tiempo de estudio, dificultad de asistir a los laboratorios, ausencia de interacción entre pares, dificultades para estudiar ciencias a distancia, dificultad del examen presencial, escasa capacidad de respuesta del centro de estudios.…”
Section: Los Resultados Las Causasunclassified
“…The students come from a diverse range of study, socioeconomic, cultural, age and ethnic backgrounds, representing 39 degree programs, encompassing all faculties across the university. The challenges facing students transitioning to university are well documented in the literature including engagement, establishing friendships, fostering a sense of belonging and building relationships with teaching staff (Grebennikov & Shah, 2012;Larmar & Ingamells, 2010;Lowe & Cook, 2003;Nelson, Quinn, Marrington, & Clarke, 2012). Many researchers cite engagement both in the social and academic aspects of university life as important predictors of student success and retention (Larmar & Ingamells, 2010;Lowe & Cook, 2003;Nelson et al, 2012).…”
Section: The Move To Inquiry-based Learning At Flinders Universitymentioning
confidence: 99%
“…Students in the study reported a 90% agreement that positive relationships with their professors encouraged persistence and 86% agreed positive course experiences in their major field of study encouraged persistence. Lack of social integration also was found to be one of ten main contributing factors of student attrition in a mixed methods study by Grebennikov and Shah (2012).…”
Section: Student Levelmentioning
confidence: 96%
“…Considering the mean age of employed students in the study was 30.63, whereas the mean age of nonworking students was 21.64, it is fair to presume older students have more employment commitments resulting in higher risks of attrition. This is echoed in an Australian mixed methods study by Grebennikov and Shah (2012) who found students who revealed more pressures from employment commitments and scheduling conflicts tended to be over 21 years old. In addition to identifying students most at risk of dropping out due to employment commitments and scheduling conflicts being non-traditionally aged, Grebennikov and Shah found two out of ten significant reasons students were not retained after their first year of college included employment commitments and scheduling conflicts.…”
Section: Employment Commitments and Family Obligationsmentioning
confidence: 96%
See 1 more Smart Citation